Unholy War: Violent Extremism in Marawi and Its Impacts on Muslim Communities in Indonesia - A.S. Hikam, Muhammad; Munabari, Fahlesa (KnE Social Sciences, 2022)
Religious radicalism in the form of violent extremism is against the principles of human rights and democracy. Religious radicalism also opposes the existence of the modern state of Indonesia and, arguably, also of other Southeast Asian countries. The global political commitment initiated by the United Nations, namely Responsibility to Protect, states that several countries in Southeast Asia, such as the Philippines, are at high risk of atrocities. Civilians in Marawi in the Philippines have experienced atrocities carried out by the Maute family-led militant group backed by the Islamic State of Iraq and Syria (ISIS). In 2017, for more than five months, the restoration of regional security and stability in Marawi by the Philippine security apparatus caused many casualties. This study aimed to identify, map and analyze the narrative structure of the goals and backgrounds of the actors involved in the Marawi case and its impacts on Muslim communities in Indonesia. The research focused on a narrative analysis that united various factors contributing to violent religious extremism. This study employed a narrative perspective that was multidimensional, consisting of the narratives of marginalization, invitation, symbolic violence, and violent extremism. It demonstrated that the narrative of marginalization and calls for Jihad served as the basis of solidarity among the members of the Maute militant group in Marawi. The narrative aimed at solidarity for jihad in Marawi had more influence on groups belonging to ISIS, such as Jamaah Ansharut Tauhid (JAT), Jamaah Ansharut Daulah (JAD), and East Indonesia Mujahideen (MIT). Keywords: violent extremism, radicalism, terrorism, Marawi, the Philippines, Indonesia